Strenghtening Families as A Strategy to Support Nation-State - Waryono Abdul Ghafur (Universitas Islam Negeri Sunan Kalijaga, 2019)
This paper was written to present the role of the biggest Islamic religious organizations in Indonesia, Muhammadiyah and NU, in supporting the nation-state through their roles in strengthening families. Family is the smallest social unit in the society that is a base of the formation of all institutions including the nation-state. Therefore, a nation-state genealogically and sociologically appeared and was formed from some units of families that agree with and bind to each other to live together in an area. As a foundation, family situation becomes the determinant of a nation-state existence and sustainability. A family that is strong and has resiliency will realize a nation-state that is strong and has endurance. On the other hand, if the base of a unit, which is a family, is weak, the nation-state will be easily collapsed. On the basis of the importance of families for the nation-state, the Indonesian government has set the rules, the government regulations, and the minister regulations on family development, such as the Acts No. 10 of 1992 on Family Development. An analysis with sociological approach on some rules above is sufficient for a proof that the state or the government is concerned much at family development. The state even has made the marriage law for the Moslems – as the majority – although based on al-Qur’an and Hadith, Islam has very clearly ruled how to build families. Two Islamic societal organizations, NU and Muhammadiyah, also have the concept of family building, which are maslahah family and sakinah family. Studies on some rules and concepts related to families have found that all parties commit to realize the family destination, in which a family has toughness and strength in religious, economic, environmental, and social aspects, so that the family functions like the religious function are really guaranteed; families become the center and also the source of varied virtue and glory. Some facts have been found, which are not a few, about collapsed families and households, but the roles of the state and the societal organizations in strengthening families are sufficient to stem the flow of the destruction of a nation-state. Tough families become the main factor of supporting the toughness and strength of the nation-state.